2009
DOI: 10.1007/s00011-009-0016-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of galectin-3 in patients with inflammatory bowel diseases: new serum marker of active forms of IBD?

Abstract: Enhanced concentration of galectin-3 in serum reflects presence of disease and points to its involvement in the pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 48 publications
4
35
0
1
Order By: Relevance
“…There are reports where galectin-3 has been utilized as a marker to follow the inflammatory activity of a disease or used as a factor for prognosis in cancers or chronic heart failure [68][70]. Serum levels of galectin-3 have been used to monitor the inflammatory stage of inflammatory bowel disease [71]. Our finding that the expression of galectin-3 is increased in HP and SARC in BAL is in line with its role in inflammation.…”
Section: Discussionsupporting
confidence: 78%
“…There are reports where galectin-3 has been utilized as a marker to follow the inflammatory activity of a disease or used as a factor for prognosis in cancers or chronic heart failure [68][70]. Serum levels of galectin-3 have been used to monitor the inflammatory stage of inflammatory bowel disease [71]. Our finding that the expression of galectin-3 is increased in HP and SARC in BAL is in line with its role in inflammation.…”
Section: Discussionsupporting
confidence: 78%
“…Galectin-3 levels in healthy adult plasma average at 12 ng/ml [15,21] and increases 3 to 5-fold as a result of different pathologies and inflammatory processes [14-17]. No reports have so far been published on the normal galectin-3 levels in neonatal plasma, why we evaluated the amount in cord blood plasma after CS.…”
Section: Resultsmentioning
confidence: 99%
“…Galectin-3 has emerged as an important marker in several settings of inflammation [14-17]. In the context of perinatal biology, we have found that galectin-3 contributes to brain injury in a murine model of hypoxic ischemia [18] and is found in increased amounts in asphyxiated infants with abnormal outcome [19].…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important disease-exacerbating role in autoimmune/inflammatory and malignant diseases (5-9) but has a protective role in obesity-induced inflammation and type 2 diabetes, as well as in primary biliary cirrhosis (10,11). Recently, several clinical studies showed a correlation between the serum level of Gal-3 and exacerbation of acute colitis, indicating the importance of Gal-3 as a potential marker for this disease (12)(13)(14). Serum concentrations of Gal-3 were significantly increased in specimens from patients with the active form of UC (12).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several clinical studies showed a correlation between the serum level of Gal-3 and exacerbation of acute colitis, indicating the importance of Gal-3 as a potential marker for this disease (12)(13)(14). Serum concentrations of Gal-3 were significantly increased in specimens from patients with the active form of UC (12). Recently, we showed that Gal-3 plays an important proinflammatory role in the induction phase of acute DSSinduced colitis by promoting activation of the NLRP3 inflammasome and production of IL-1β in macrophages (7).…”
Section: Introductionmentioning
confidence: 99%